The Role of Social Media in Supporting The Existence of Libraries - Rusadi, La Ode; Fendy (Jurnal Diskursus Islam, 2023)
The application of information technology devices to a library is the most effective step or indicator in terms of spreading the existence of a library in supporting the process of learning activities both at the elementary school level and at the tertiary level. Therefore, in this paper, the author will discuss and examine how the role of social media will be involved and support in disseminating the information needed by users as well as this social media will support the existence of a library. Because in the author's observation at this time, the intensity of the use of social media in the technological era is so great that this media can be utilized as a means of disseminating information around the Library. So that the fulfilment of the need to search for and find information can be obtained quickly and easily